Kesulitan Belajar Mahasiswa dalam Kuliah Daring selama Masa Pandemi Covid-19 - Ajeng Widyaningrum; Dwi Ratnasari; Alfauzan Amin; Veron Pratama (Pendidikan Agama Islam STIT Palapa Nusantara, 2022)
This study aims to obtain objective information about the learning difficulties of UIN Islamic Religious Education student Fatmawati Sukarno Bengkulu in online lectures during the Covid-19 pandemic. This research uses descriptive qualitative methods. The data collection technique used uses indirect communication techniques with data collection tools through the dissemination of interviews using Whatsapp. The informants in this study were 22 students consisting of active students of Islamic Religious Education UIN Fatmawati Sukarno Bengkulu class of 2020/2021. The results obtained from this study show that the difficulty of learning Islamic Religious Education in online lectures during the Covid-19 pandemic is very diverse. The various difficulties of online learning include the effectiveness of the teaching and learning process and also technical obstacles such as unstable internet networks, limited access to the internet, limited quotas, and lack of inetraktion during the online learning process.